Colorimetric detection of acidic pesticides in water. Issue 7 (23rd December 2021) - Smith, Kyle T.; Ramsperger, Chloe A.; Hunter, Kye E.; Zuehlsdorff, Tim J.; Stylianou, Kyriakos C.
Abstract : A water stable, porphyrin-based metal–organic framework as a colorimetric sensor for the detection of acidic pesticides. Abstract : A water-stable, porphyrin-based metal–organic framework (MOF) produces a distinct colour change in response to acids' p K a and concentrations. This colour change is associated with the protonation of the N-atoms within the porphyrin ligand present in the MOF structure. As a proof-of-concept, we demonstrate the use of this MOF for detecting traces of different acidic pesticides present in water samples spontaneously.